4x^2 -2x +6 x x +3 -------------------- 12x^2 -6x 18 4x^3 -2x^2 +6x = 4x^3 8x^2 +0x +18 If -6 +6 =0 Why doesn't x -x =0
Last edited by Leona_Marie; Jan 20th 2009 at 07:58 PM.
Follow Math Help Forum on Facebook and Google+
Originally Posted by Leona_Marie 4x^2 -2x +6 x x +3 -------------------- 12x^2 -6x 18 4x^3 -2x^2 +6x = 4x^3 8x^2 +0x +18 If -6 +6 =0 Why doesn't x -x =0 I really can't make sense of your post. What are you trying to do?
Originally Posted by Leona_Marie 4x^2 -2x +6 x x +3 -------------------- 12x^2 -6x 18 4x^3 -2x^2 +6x = 4x^3 8x^2 +0x +18 If -6 +6 =0 Why doesn't x -x =0 Ahhh I see. $\displaystyle (x+3)(4x^2-2x+6) = x(4x^2-2x+6)+3(4x^2-2x+6) $ $\displaystyle = 4x^3-2x^2+6x+12x^2-6x+18 $ $\displaystyle = 4x^3+10x^2+18 $ $\displaystyle x - x $ DOES equal zero :S.
Originally Posted by Mush Ahhh I see. $\displaystyle (x+3)(4x^2-2x+6) = x(4x^2-2x+6)+3(4x^2-2x+6) $ $\displaystyle = 4x^3-2x^2+6x+12x^2-6x+18 $ $\displaystyle = 4x^3+10x^2+18 $ $\displaystyle x - x $ DOES equal zero :S. sorry thats not how I typed it. Im still learing my polys so when I do a problem then look at the answer sometimes they confuse me with bad answers... thats why I ask. thankyou
View Tag Cloud